Prey utilisation and trophic overlap between the non native mosquitofish and a native fish in two Mediterranean rivers - KALOGIANNI, E.; GIAKOUMI, S.; ANDRIOPOULOU, A.; CHATZINIKOLAOU, Y. (Mediterranean Marine Science, 2014)
Non native freshwater fish species have been long implicated in the decline of native Mediterranean ichthyofauna, through hybridization, disease transmission, competition for food and habitat, predation and/or ecosystem alteration; our knowledge, however, on the underlying mechanisms of these ecological impacts remains very limited. To explore the potential for trophic competition between the widespread Eastern mosquitofish Gambusia holbrooki and its co-occurring native toothcarp Valencia letourneuxi we compared resource use, feeding strategies, trophic selectivities and diet niche overlap. For this purpose, we studied two populations of the two species from a freshwater and a brackish habitat respectively, characterized by different food resource availabilities. In both habitats, the mosquitofish consumed a greater diversity of invertebrates and preyed on terrestrial invertebrates more frequently than the native toothcarp. Furthermore, in the less diverse and less rich brackish habitat, the non native relied heavily on plant material to balance a decrease in animal prey consumption and modified its individual feeding strategy, whereas these adaptive changes were not apparent in the native species. Their diet overlapped, indicating trophic competition, but this overlap was affected by resource availability variation; in the freshwater habitat, there was limited overlap in their diet, whereas in the brackish habitat, their diets and prey selectivities converged and there was high overlap in resource use, indicative of intense interspecific trophic competition. Overall, it appears that the underlying mechanism of the putative negative impacts of the mosquitofish on the declining Corfu toothcarp is mainly trophic competition, regulated by resource variability, though there is also evidence of larvae predation by the mosquitofish.